Blood Volume, Hemoglobin Mass, and Peak Oxygen Uptake in Older Adults: The Generation 100 Study - Lundgren, Kari Margrethe; Aspvik, Nils Petter; Langlo, Knut Asbjørn Rise; Braaten, Tonje; Wisløff, Ulrik; Stensvold, Dorthe; Karlsen, Trine (Frontiers in Sports and Active Living, 2021)
Purpose: To investigate the association between blood volume, hemoglobin mass, and peak oxygen uptake (VO2peak) in healthy older adults. Methods: Fifty participants from the prospective randomized Generation 100 Study (n =1566) were categorized as fit or unfit (age and sex-specific VO2peak above or below average values). Blood, plasma and erythrocyte volume and hemoglobin mass were tested using the carbon monoxide rebreathing method within one week after VO2peak testing. Results: Mean age, BMI, and VO2peak were 73.0 +- 2.1 years, 24.8 +- 3.3 kgxm2 and 33.5 +- 8.4 mLxkg-1xmin-1, and mean fit and unfit VO2peak were 51.4+-5.9 and 36.5+-3.3 mLxkg-1xmin-1, respectively. The fit group was younger (delta 1.3 years), leaner (delta 3.0 BMI), and more physically active (delta 3480 stepsxday-1) than the unfit group (P<0.005). Relative to body weight, blood, plasma, erythrocyte volume, and hemoglobin mass were significantly higher in the fit group (P<0.05). Hemoglobin mass and erythrocyte volume explained 40% and 37%, respectively, of the variability in VO2peak, with a limited effect of physical-activity adjustment (40% and 38%, respectively). Blood and plasma volume explained 15% and 25%, respectively, of VO2peak variability, and the association was strengthened adjusting for physical activity (25% and 31%, respectively), indicating a training-dependent adaptation in plasma but not erythrocyte volume (p  0.006). Conclusions: Blood and plasma volumes were moderately associated with VO2peak in healthy older men and women, and the association was strengthened after adjustment for physical activity. Hemoglobin mass and erythrocyte volume were strongly associated with VO2peak but unrelated to current physical activity.